The Issues of the Heritage ("Valiaxd") in the Khanate of Khiva - Begaliyeva Dilfuza Egamqulova (International Journal on Integrated Education, 2022)
The article examines the choice of heir to the throne in the late medieval era in the Khiva Khanate, the spiritual and physical maturity of the princes, and their preparation for governing the state.